RSMA-Based Bistatic ISAC Framework for LEO Satellite Systems - Park, Juha; Seong, Jaehyup; Ryu, Jaehak; Mao, Yijie; Shin, Wonjae (IEEE International Conference on Communications workshops, 2024)
To provide ubiquitous global connectivity and target detection on the same platform, a low Earth orbit (LEO) satellite system simultaneously performing communication and radar tasks has drawn significant attention. However, the design of such a joint system should address the challenges of limited power resources on satellites and inter-/intra-function interference. In this paper, we put forth a novel LEO satellite-based bistatic integrated sensing and communication (ISAC) framework that can overcome severe echo path loss by introducing a radar receiver separated from the satellite, thus reducing the satellite's power consumption burden. To effectively manage inter-/intra-function interference, which is a critical factor that can deteriorate system performance, we employ rate-splitting multiple access (RSMA). In RSMA, each user's message is split and encoded into individual private and common streams. We jointly optimize power and beamforming design for the dual-functional signal based on the rate-splitting approach. Numerical results show that the proposed framework enables superior interference control capability and significantly reduces echo path loss compared to several benchmarks. Furthermore, it is validated that the common stream serves three key roles: i) forming a beam towards the radar target, ii) controlling interference between radar and communication functions, and iii) managing interference among communication users. By doing so, efficient joint operation is achieved even without a dedicated radar signal, thanks to the multi-functionality of the common streams under limited spectral and hardware resources.